A bonding model for gold(I) carbene complexes - Benitez, Diego (2009)
The last decade has witnessed dramatic growth in the number of reactions catalyzed by electrophilic gold complexes. While proposed mechanisms often invoke the intermediacy of gold-stabilized cationic species, the nature of bonding in these intermediates remains unclear. Herein, we propose that the carbon-gold bond in these intermediates is comprised of varying degrees of both σ and π-bonding; however, the overall bond order is generally less than or equal to unity. The bonding in a given gold-stabilized intermediate, and the position of this intermediate on a continuum ranging from gold-stabilized singlet carbene to gold-coordinated carbocation, is dictated by the carbene substituents and the ancillary ligand. Experiments show that the correlation between bonding and reactivity is reflected in the yield of gold-catalyzed cyclopropanation reactions.